Attention deficit and hyperactivity disorder, methylphenidate, and epilepsy. Issue 1 (21st December 2004) - Tan, M; Appleton, R
Abstract : Attention deficit hyperactivity disorder (ADHD) is characterised by inattention, impulsivity, and hyperactivity. The DSM-IV diagnosis of ADHD requires the presence of six of nine items or features that must have been present for at least six months, to have had an onset before 7 years of age, and to have resulted in significant distress or impairment.1 In the general population, the prevalence of ADHD is approximately 5%.2 There is a high co-morbidity of epilepsy and attentional and behavioural problems, 3, 4 including ADHD, and it has been estimated that at least 20% of patients with epilepsy may present with features of ADHD.5